Effect of Topical Applications of Oils Extracted from Medicinal Plants and Coconut Oil Mixed with Egg Yolk and Vitamin E On Growth of Rabbit Hair of District Karak, Khyber Pakhtunkhwa, Pakistan (Texas Journal of Agriculture and Biological Sciences, 2022)
Most people have little awareness about how to appropriately care for their hair and scalp. Healthy hair and healthy scalp typically complement each other, so a healthy scalp is needed to give the appearance of healthy hair and vice versa. Genetic and hormonal changes are important factors in hair loss, but weathering and grooming habits take a toll on our hair as well. The present study was designed to investigate the effect of the hair growth promoting effects of oil extracted from Amla, rittha and sikha Kai and effect of coconut oil mixed with egg yolk and vitamin E in male rabbits. Five healthy adult male rabbits were included in this study. Plant oil were extracted by direct boiling method while coconut oil was mixed with egg yolk (1:1 ratio) and vitamin E. Animals hair were trimmed at three points (back and lateral sides) with razor blades (1x1 inch each) on experimental day one. The points were randomly allocated for oil application